Acoustic reflexes are common but not pervasive: evidence using a diagnostic middle ear analyser. (26th January 2018) - McGregor, Kara D.; Flamme, Gregory A.; Tasko, Stephen M.; Deiters, Kristy K.; Ahroon, William A.; Themann, Christa L.; Murphy, William J.
Abstract: Objective : The objective of this study is to determine whether acoustic reflexes are pervasive (i.e. known with 95% confidence to be observed in at least 95% of people) by examining the frequency of occurrence using a friction-fit diagnostic middle ear analyser. Design : Adult participants with very good hearing sensitivity underwent audiometric and middle ear testing. Acoustic reflexes were tested ipsilaterally and contralaterally in both ears across a range of elicitor frequencies. Reflex elicitors were 700 ms tones presented at maximum level of 100 dB HL. Two automated methods were used to detect the presence of an acoustic reflex. Study sample : A group of 285 adult volunteers with normal hearing. Results : There were no conditions in which the proportion of participants exhibiting acoustic reflexes was high enough to be deemed pervasive. Ipsilateral reflexes were more likely to be observed than contralateral reflexes and reflexes were more common at 0.5 and 1 kHz elicitor frequencies as compared with 2 and 4 kHz elicitor frequencies. Conclusions : Acoustic reflexes are common among individuals with good hearing. However, acoustic reflexes are not pervasive and should not be included in damage risk criteria and health hazard assessments for impulsive noise.